Simulation for production of syariah-compliant influenza vaccine using trypsin and Acutase in batch reactor via Superpro Designer - Fatin Nur Aliya Mohamad Ros,; Norliza Abd Rahman,; Nurina Anuar,; Jarinah Mohd Ali,; Muhammad Amirul Irwan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The halal status of the vaccine is being questionable among the Muslim community around the world. Some of them even took a risk not to take the vaccine when this issue is resurrected. This is due to the uses of porcine trypsin that comes from the prohibited animals which is pancreas (pig). The main aim of this study is to find the effectiveness of alternative enzyme (Acutase™) that comes from invertebrate sources in replacing the trypsin™ enzyme. Two modes of operation which are batch and continuous mode were compared to determine the high production rate of the vaccines. The production of syariah-compliant vaccine mainly focused on the bioreactor and simulated by using a software called SuperPro® Designer. The different reactions of time ranging from 1-5 days were tested to each enzyme. The hemagglutinin (HA) concentration gained will form the growth curves of the cell. The HA concentration data from the simulation indicates the number of cell growth in the cell culture process. Result shows a batch reactor can achieve until 60% of the yield production. The curves show the highest concentration of cell by using Acutase™ is at day 3 which is 1.17 X 106 cells/mL. Meanwhile, 0.98 x 106 cells/mL produced by trypsin enzyme at day 4. Total hemagglutinin produced is calculated by using the following standard condition, 1 HA unit corresponds to 104 cells per mL. Therefore, the hemagglutinin (HA) concentration produced by using acutase™ is 117 Unit HA compared to the trypsin™ which is 98.8 Unit HA. The results prove that the production of syariah compliant influenza vaccine can be produced in the future and enhance the uses of the vaccine among Muslim community.